2010
DOI: 10.1111/j.1600-0528.2010.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a multilevel model of young children’s oral health with national survey data

Abstract: Objectives-To empirically test a multilevel conceptual model of children's oral health incorporating 22 domains of children's oral health across four levels: child, family, neighborhood and state. Study design-We examined child-, family-, neighborhood-, and state-level factors influencing parent's report of children's oral health using a multilevel logistic regression model, estimated for 26 736 children ages 1-5 years.Principal findings-Factors operating at all four levels were associated with the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 35 publications
1
49
2
2
Order By: Relevance
“…In addition to their conceptual relevance for both dentist location decisions and parents access and use of dental care, several of these factors have been shown to be relevant for oral health, including in this sample. 18,20,25 In an alternative model, we included an aggregate index of neighborhood quality derived from these variables (generated using principal component analysis), but this had no effect on the results for dentist supply (details available upon request).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their conceptual relevance for both dentist location decisions and parents access and use of dental care, several of these factors have been shown to be relevant for oral health, including in this sample. 18,20,25 In an alternative model, we included an aggregate index of neighborhood quality derived from these variables (generated using principal component analysis), but this had no effect on the results for dentist supply (details available upon request).…”
Section: Discussionmentioning
confidence: 99%
“…Both conceptual frameworks (FisherOwens et al, 2007;Bramlett et al, 2010) and scientific evidence support the hypothesis that caregivers' low health literacy may be associated with the use of tertiary dental services for their children, which can translate to increased expenditures for oral-health-related services and/or specifically restorative and emergency dental services. In our previous investigations, we have found low caregiver literacy to be linked to poorer child oral health outcomes and more detrimental oral-health-related behaviors, including worse oral health status Vann et al, 2010), knowledge (Hom et al, 2012), child oralhealth-related quality of life (Divaris et al, 2012a), and deleterious feeding practices .…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, there are few studies and conflicting evidence about the association of contextual effect on oral health in preschool children Aida et al, 2008;Pereira et al, 2010;Borrell and Baquero, 2011;Borenstein et al, 2013;Martins et al, 2014]. While a study demonstrated a strong influence of contextual factors on dental caries among preschool children [Aida et al, 2008], others showed a weak or no effect, mainly when individual variables were included as controls [Bramlett et al, 2010;Piovesan et al, 2011].…”
mentioning
confidence: 99%